2011
DOI: 10.1007/s13344-011-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of vortex-induced vibration of a circular cylinder near a deformable wall with two degrees of freedom in steady flow

Abstract: The behavior of vortex-induced vibration of a two-degree-of-freedom cylinder near a deformable wall in steady flow is investigated experimentally. The typical phenomenon of the two-degree-of-freedom cylinder's VIV is discussed. The influences of initial gap between the cylinder and the wall on the dynamic responses of the cylinder are analyzed. The comparison is made about dynamic responses of the cylinder with one and two degrees of freedom. Experimental results show that the vibration of the cylinder near a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Similar to the trend for A max y =D, as e/D decreases, there is an increase in the U n at which the peak A rms x =D occurs. In Yang et al (2011), peak A rms x =D increases with a decrease in e/D, and a similar increase in U n at which the peak amplitudes occur is observed.…”
Section: Transverse and Streamwise Amplitudesmentioning
confidence: 58%
See 1 more Smart Citation
“…Similar to the trend for A max y =D, as e/D decreases, there is an increase in the U n at which the peak A rms x =D occurs. In Yang et al (2011), peak A rms x =D increases with a decrease in e/D, and a similar increase in U n at which the peak amplitudes occur is observed.…”
Section: Transverse and Streamwise Amplitudesmentioning
confidence: 58%
“…Yang et al (2008) studied experimentally 2-DoF VIV of near-wall cylinder in the turbulent regime, where they found a decrease in vibration amplitudes with decreasing e/D. Yang et al (2011) compared the dynamic response of cylinder near a deformable wall in both 1-DoF and 2-DoF cases. Yang et al (2009) showed that the dimensionless vibration frequency for smaller e/D of 0.06 and 0.30 are much larger than those for larger e/D of 0.66 and 0.88, respectively, at the same reduced velocity.…”
Section: Introductionmentioning
confidence: 99%
“…While Ur is from 3 to 8, the deviation between the two frequencies is considerable. Yang and Gao discovered a reduction in transverse vibration amplitudes with reducing gap ratio G/D by studying the VIV of a cylinder near a wall in the turbulent regime in an experiment 7) . Yang and Gao discovered experimentally that vibration range increases with reducing mass ratio m*.…”
Section: Introductionmentioning
confidence: 99%